The Effectiveness of RADEC Learning Model to Improve HOTS (Higher Order Thinking Skill) in Insya’ Learning: Efektivitas Model Pembelajaran RADEC untuk Meningkatkan HOTS (Higher Order Thinking Skill) pada Pembelajaran Insya’ - Etri Suryanti; Muhammad Ihsan; Anwar Ridwan Nulloh; Arief Yahya Sulaeman; Isop Syafei; Usup Suparman (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
HOTS (Higher Order Thinking Skill) is necessary for living in the 21st century. In this century, routine work will be charged to robots, while humans will be charged with creative work. In order to avoid being eroded by the times, HOTS needs to be developed even since elementary school. Therefore, there is a need for methods, strategies, or learning models that can improve student HOTS. Researchers conducted a study to test the effectiveness of implementing the RADEC learning model in improving students' HOTS in learning Insya’; the material translates the text, and how students respond to the learning model. The research method used is quasi-experimental, with the research design of a nonequivalent Control Group. The results showed that it took 135 minutes to implement the RADEC learning model in learning Insya’ material translating text in PP Darussalam. The improvement in higher-order thinking skills (HOTS) after receiving treatment is reported to be 49%, which is classified as a sufficient category. Nevertheless, the RADEC learning model is still considered more effective in enhancing HOTS than the classical model, and the participants' response to this model is highly positive, reaching 81%. Further research on the RADEC learning model, using an equivalent comparative model, is needed to strengthen its effectiveness in enhancing HOTS. Keywords: HOTS (Higher Order Thinking Skill), Translating Text, RADEC Learning Model, Insya’ Learning.   Abstrak HOTS (Higher Order Thinking Skill) merupakan keterampilan yang diperlukan untuk hidup di abad 21. Pada abad ini, pekerjaan rutinitas akan dibebankan kepada robot, sedangkan manusia akan dibebankan pekerjaan kreatif. Agar tidak tergerus oleh zaman, HOTS perlu dikembangkan bahkan sejak duduk di bangku sekolah dasar. Karena itu, perlu adanya metode, strategi, atau model pembelajaran yang dapat meningkatkan HOTS peserta didik. Peneliti melakukan sebuah penelitian untuk menguji efektivitas implementasi model pembelajaran RADEC dalam meningkatkan HOTS peserta didik pada pembelajaran Insya’ materi menerjemahkan teks serta bagaimana respon peserta didik terhadap model pembelajaran tersebut. Metode penelitian yang digunakan adalah metode kuasi eksperimen dengan desain penelitian The Nonequivalent Control Group. Hasil penelitian menunjukkan bahwa diperlukan waktu 135 menit untuk mengimplementasikan model pembelajaran RADEC pada pembelajaran Insya’ materi menerjemahkan teks di PP Darussalam Kersamanah Garut. Kemudian peningkatan HOTS peserta didik setelah diberikan treatment adalah sebesar 49% yang termasuk kategori cukup. Namun demikian, model pembelajaran RADEC tetap dipandang lebih efektif dalam meningkatkan HOTS dibanding model klasik dan respon peserta didik terhadap model ini sangat positif, yaitu sebesar 81%. Perlu dilakukan penelitian lanjutan tentang model pembelajaran RADEC dengan model pembanding yang ekuivalen untuk lebih memperkuat bukti efektivitas model pembelajaran RADEC dalam meningkatkan HOTS. Kata Kunci: HOTS (Higher Order Thinking Skill), Menerjemahkan Teks, Model Pembelajaran RADEC, Pembelajaran Insya.